Scoping Review of Transformative Agreement Research - Riegelman, Amy; Langham-Putrow, Allison (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2025)
Objective – Transformative agreements (TAs) are agreements between publishers and institutions or consortia that combine reading access and open access (OA) publishing. They can take many forms, and the first agreement is believed to have started in 2014. This scoping review aims to identify and synthesize the existing research on TAs.Methods – Following benchmarking and term harvesting, electronic searches were conducted in 48 databases and were complemented with handsearching and citation chaining which resulted in 1843 unique results. Results were screened with pre-registered inclusion and exclusion criteria which resulted in inclusion of 151 studies (80 case studies, 39 quantitative, 31 qualitative, and 1 theoretical).Results – The heterogeneity of methods and findings of research on TAs made synthesis challenging. The synthesis was further complicated by the corpus including studies examining different time periods, publishers, agreement types, participating institutions, and more. Studies had varied intended audiences and research dissemination routes further complicating discovery and synthesis.Conclusions – Despite the heterogeneity, some themes emerged, including TAs increase hybrid OA and that consortia can play an important role in negotiating and managing TAs. Successful implementation relies on a number of factors, including workflows for authors and those managing the agreements. Studies found that TAs are not leading to a transformation of the publishing system as a whole.